Individual variation in the frequency of sperm aneuploidy in humans - Rubes, J; Vozdova, M; Oracova, E; Perreault, S D (Cytogenetic and genome research, 2005)
To examine interindividual differences in sperm chromosome aneuploidy, repeated semen specimens were obtained from a group of ten healthy men, aged 20-21 at the start of the study, and analyzed by multi-color fluorescence in situ hybridization (FISH) analysis to determine the frequencies of sperm aneuploidy for chromosomes X, Y, 8, 18 and 21 and of diploidy. Semen samples were obtained three times over a five-year period. Statistical analysis examining the stability of sperm aneuploidy over time by type and chromosome identified two men who consistently exhibited elevated frequencies of sperm aneuploidy (stable variants): one with elevated disomy 18 and one with elevated MII diploidy. Differences among frequencies of aneuploidy by chromosome were also seen. Overall, disomy frequencies were lower for chromosome X, 8 and 18 than for chromosomes 21 or Y and for XY aneuploidy. The frequency of chromosome Y disomy did not differ from XY sperm frequency. Also, the frequency of meiosis I (XY) and II (YY + XX) sex chromosome errors did not differ in haploid sperm, but the frequency of MII errors was lower than MI errors in diploid sperm. Frequencies of sperm aneuploidy were similar between the first sampling period and the second, two years later. However, the frequency of some types of aneuploidy (XY, disomy Y, disomy 8, total autosomal disomies, total diploidy, and subcategories of diploidy) increased significantly between the first sampling period and the last, five years later, while others remained unchanged (disomy X, 21 and 18). These findings confirm inter-chromosome differences in the frequencies of disomy and suggest that some apparently healthy men exhibit consistently elevated frequencies of specific sperm aneuplodies. Furthermore, time/age-related changes in sperm aneuploidy may be detected over as short a period as five years in a repeated-measures study.
Keywords: dospělí; aneuploidie; spermie; Adult; Semen; Spermatozoa; uniparentální disomie; lidé; Uniparental Disomy; motilita spermií; sperma; Sperm Count; Male; hybridizace in situ fluorescenční; Sperm Motility; mužské pohlaví; Aneuploidy; In Situ Hybridization, Fluorescence; počet spermií; Humans